2016
DOI: 10.1007/s10676-016-9387-z
|View full text |Cite
|
Sign up to set email alerts
|

Should we welcome robot teachers?

Abstract: Current uses of robots in classrooms are reviewed and used to characterise four scenarios: (s1) Robot as Classroom Teacher; (s2) Robot as Companion and Peer; (s3) Robot as Care-eliciting Companion; and (s4) Telepresence Robot Teacher. The main ethical concerns associated with robot teachers are identified as: privacy; attachment, deception, and loss of human contact; and control and accountability. These are discussed in terms of the four identified scenarios. It is argued that classroom robots are likely to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
189
0
10

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(201 citation statements)
references
References 49 publications
2
189
0
10
Order By: Relevance
“…This builds on previous and concurrent investigations by other researchers into emotional assistance for people with dementia, particularly evident in the aforementioned area of socially assistive robotics (Begum et al 2015;Sharkey 2014Sharkey , 2016; Aimee van Wynsberghe 2013; A van Wynsberghe 2015). Experiments have been undertaken with various aspects of usability and interfacing, including telepresence where screens display human-like faces (Begum et al 2015), robots that appear human and others that provide audio responses, including ones that appear as pets which talk, such as the Gerijoy avatars for people with dementia, mentioned above.…”
Section: Emotion Design Considerationssupporting
confidence: 57%
“…This builds on previous and concurrent investigations by other researchers into emotional assistance for people with dementia, particularly evident in the aforementioned area of socially assistive robotics (Begum et al 2015;Sharkey 2014Sharkey , 2016; Aimee van Wynsberghe 2013; A van Wynsberghe 2015). Experiments have been undertaken with various aspects of usability and interfacing, including telepresence where screens display human-like faces (Begum et al 2015), robots that appear human and others that provide audio responses, including ones that appear as pets which talk, such as the Gerijoy avatars for people with dementia, mentioned above.…”
Section: Emotion Design Considerationssupporting
confidence: 57%
“…Nevertheless, technology-driven ethical appraisals are not child-centered, and seldom take into consideration the possibility of detrimental effects on child development or the wider social context (e.g., the home or the school). In contrast, psychology-driven ethical appraisals such as outlined by Amanda and Noel Sharkey [45,46] do highlight issues of emotional attachment, deception of the child, and loss of human contact (see also [33]). Apropos teachers' attitudes to robots in the classroom, research reported in [47] demonstrates the exigency of taking the consideration of ethics beyond design issues and toward engagement with stakeholders' views on how robots may affect their current practices.…”
Section: How Could Biases Of the Technological Imagination Be Avoided?mentioning
confidence: 99%
“…Although I have doubts about whether a robot can be a moral agent, the appearance of moral agency is enough to warrant ethical evaluation. Furthermore, these robots are being placed into contexts in which they are responsible for children (educational robots and social robots) (Sharkey 2016), our grandparents (Sharkey and Sharkey 2012), and other vulnerable demographics. These contexts are, like healthcare, inherently ethical.…”
Section: Service Robots: What and Why?mentioning
confidence: 99%